2016
DOI: 10.1002/etc.3562
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis of potential stressors adversely affecting benthic invertebrate communities in Greenwich Bay, Rhode Island, USA

Abstract: Greenwich Bay is an urbanized embayment of Narragansett Bay potentially impacted by multiple stressors. The present study identified the important stressors affecting Greenwich Bay benthic fauna. First, existing data and information were used to confirm that the waterbody was impaired. Second, the presence of source, stressor, and effect were established. Then linkages between source, stressor, and effect were developed. This allows identification of probable stressors adversely affecting the waterbody. Three … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 35 publications
(54 reference statements)
0
5
0
Order By: Relevance
“…Many suspension- and filter-feeders frequently face turbid environments with high concentrations of non-caloric materials generated by natural processes, such as terrestrial runoff, currents, and weather-induced bottom sediment resuspension 55 , but also by anthropogenic activities, such as dredging and capping of contaminated sediments using various technologies. In aquatic ecology, conditions with elevated suspended solids are commonly acknowledged as stressful 56 and regulated by water quality standards 21,57 . The quality standards vary across regions and types of aquatic systems, e.g., lotic and lentic, as well as systems with different natural levels of suspended solids.…”
Section: Discussionmentioning
confidence: 99%
“…Many suspension- and filter-feeders frequently face turbid environments with high concentrations of non-caloric materials generated by natural processes, such as terrestrial runoff, currents, and weather-induced bottom sediment resuspension 55 , but also by anthropogenic activities, such as dredging and capping of contaminated sediments using various technologies. In aquatic ecology, conditions with elevated suspended solids are commonly acknowledged as stressful 56 and regulated by water quality standards 21,57 . The quality standards vary across regions and types of aquatic systems, e.g., lotic and lentic, as well as systems with different natural levels of suspended solids.…”
Section: Discussionmentioning
confidence: 99%
“…The head of the Bay, located in a highly urbanized area, is highly eutrophic while trophic levels at the mouth are more similar to those found over the continental shelf [ 12 , 13 ]. Previous studies have shown that eutrophication in the headwaters of Narragansett Bay affects many local communities and ecosystem processes at locations downstream, including nitrification rates [ 14 ], primary productivity [ 15 ], animal physiology, and benthic biodiversity [ 16 , 17 ]. Over the last 20 years, Narragansett Bay has undergone dramatic changes as a result of targeted efforts to reduce nutrient loading, providing a dynamic model for the study of gradients in estuarine eutrophication [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Regional factors may be more important than local factors in driving changes at North Jamestown while local pollution factors may be a stronger influence in driving changes at Spar Island. The two sites we used complement studies of benthic community trends in two other impacted areas of upper Narragansett Bay -Greenwich Bay and the Providence and Seekonk Rivers (Calabretta and Oviatt, 2008;Pelletier et al, 2017). Like Mount Hope Bay, Greenwich Bay is another sub-embayment that has shown few signs of ecosystem recovery (Pesch et al, 2012;Pelletier et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the Kruskal-Wallis test indicated that variance of Δ* was influenced by eutrophication (water column chlorophyll a, sediment TOC) and by sediment contaminants. Although correlations do not prove causation, these stressors are known to affect community composition (Jeon and Oviatt, 1991;Snelgrove et al, 2004;Diaz et al, 2008;Tweedley et al, 2015;Hale et al, 2016;MERL, 2017;Pelletier et al, 2017). Although moderate levels of nitrogen and sediment TOC support secondary production, too-high levels can lead to seasonal hypoxia and degraded sediment habitat, as exists in much of the upper third of the bay (Saarman et al, 2008).…”
Section: Temporal Trends Of Narragansett Bay Benthic Biodiversitymentioning
confidence: 99%
See 1 more Smart Citation